AN IN-DEPTH ANALYSIS OF DENGUE MOSQUITO DYNAMICS IN LAHORE: UNRAVELING THE IMPACT OF DENGUE OUTBREAKS AND ENVIRONMENTAL FACTORS - SHAFAE, G; ALI, M; KHAN, HAA (Biological and Clinical Sciences Research Journal, 2024)
Dengue fever, caused by the Aedes mosquito-borne dengue virus, is still a major public health concern in many parts of the world, including Lahore, Pakistan. Lahore region is regarded as a dengue fever hotspot due to the large number of cases reported each year. The purpose of this research is to give an in-depth analysis of dengue mosquito dynamics in Lahore, with a particular emphasis on determining the influence of dengue epidemics and environmental factors. The current study was based on survey comprising 240 individuals from Lahore. In the study findings, 82.08% were positive cases and 17.91% were negative cases. The majority of respondents, were aware of the symptoms of dengue infection (62.33%), its transmission (90.83%), the cause of dengue (61%), safety precautions (73.33%), and the organ infected by the dengue virus (66.25). However, the majority of people are still clueless. 70% of participants indicate that television is their primary information source. Dengue fever cases have been found to have a seasonal pattern, peaking during the monsoon season (45.41%) when mosquito breeding conditions are perfect. The study’s findings revealed that Aedes mosquitos, particularly Aedes aegypti, were widespread and identified as the primary vectors (61.66%) of dengue transmission in Lahore. It was revealed that temperature (49.58%), and rainfall all affected the number of Aedes mosquitoes. Overall, 81.6% were satisfied with Governmental efforts against the spread of dengue fever. Improved public knowledge is necessary to reduce dengue virus incidence. The findings of this study can assist public health professionals and legislators in developing targeted measures to mitigate the consequences of dengue epidemics and protect the public from this terrible infection.